Konflik Sosial dan Ancaman Radikalisme dalam Masyarakat Multikutural : Studi Kasus di Sangatta Utara, Kutai Timur - Nur Aini Hidayah; Siti Latifaturrohmah; Anis Sa’adah (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
Social conflict and religious radicalism that occurred in North Sangatta, East Kutai, as part of the dynamics of a multicultural society. The main focus of the study is the form and characteristics of social conflict in the multicultural society of North Sangatta, the form of characteristics of social conflict in the multicultural society of North Sangatta to determine the form and characteristics of social conflict that arises amidst ethnic, cultural, and religious diversity, and to analyze the extent of the role of religious leaders, local governments, and educational institutions in handling the conflict and preventing the development of radical religious understanding. The approach used is a qualitative approach with field study methods, in-depth interviews, and documentation. The results of the study show that social conflict in this area tends to be horizontal and is triggered by differences in social identity and group interests. Meanwhile, collaborative efforts between community leaders, religious institutions, and the government show an important role in building dialogue, tolerance education, and strengthening the values ​​of diversity as a form of prevention against radicalism. This study is expected to be a contribution to strengthening social integration and peace in multicultural areas.